Hepatitis B Reactivation in a HBsAg-Negative, HBcAb-Positive Patient Receiving Fludarabine for the Treatment of Chronic Lymphocytic Leukaemia - Federica Toscanini; Pasqualina De Leo; Giuseppe Calcagno; Federica Malfatti; Alessandro Grasso; Marco Anselmo (Case Reports in Hepatology)
Hepatitis B virus (HBV) reactivation is an increasingly recognized cause of morbidity and mortality in patients undergoing chemotherapy. In haematology, the risk of reactivation of B hepatitis among HBsAg-positive patients has been documented; therefore, use of lamivudine prophylaxis is recommended before starting chemotherapy. Differently, for HBsAg-negative patients with markers of previous HBV infection (i.e., presence of isolated anti-HBc positivity) (anticore patients) management strategies are not univocal. We describe a rare case of HBV reactivation in an anticore patient after fludarabine therapy for chronic lymphocytic leukaemia. The patient fully recovered after a 6-month course of lamivudine with persistent HBV-DNA clearance and loss of HBsAg. The most important feature of this case is that fludarabine alone infrequently determines HBV reactivation, especially in anticore patients. Therefore, we suggest that patients candidates to receive fludarabine therapy should be considered for lamivudine prophylaxis, not only if HBsAg-positive, but even if anticore-positive only.